2001
DOI: 10.1073/pnas.221364198
|View full text |Cite
|
Sign up to set email alerts
|

Correction of the retinal dystrophy phenotype of the RCS rat by viral gene transfer of Mertk

Abstract: The Royal College of Surgeons (RCS) rat is a widely studied animal model of retinal degeneration in which the inability of the retinal pigment epithelium (RPE) to phagocytize shed photoreceptor outer segments leads to a progressive loss of rod and cone photoreceptors. We recently used positional cloning to demonstrate that the gene Mertk likely corresponds to the retinal dystrophy (rdy) locus of the RCS rat. In the present study, we sought to determine whether gene transfer of Mertk to a RCS rat retina would r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
188
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(196 citation statements)
references
References 32 publications
2
188
0
2
Order By: Relevance
“…8,11 Immune responses to Ad vectors appear to limit their effectiveness in the eye to around 3 weeks. 10,14 Although gene replacement therapy using an AAV-2 vector is more effective than that using an Ad vector, 11 the late onset of AAV-mediated expression is likely to compromise its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…8,11 Immune responses to Ad vectors appear to limit their effectiveness in the eye to around 3 weeks. 10,14 Although gene replacement therapy using an AAV-2 vector is more effective than that using an Ad vector, 11 the late onset of AAV-mediated expression is likely to compromise its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The first demonstration of successful rescue of both a functional cellular defect (phagocytosis) and a photoreceptor degeneration was achieved by recombinant adenovirus-mediated gene transfer to the RPE. 78 More recently, it was demonstrated that rAAV-mediated gene transfer slows photoreceptor loss in this model. Subretinal injection of rAAV-2/2mertk prolong photoreceptor cell survival in the RCS rat, as assessed by histology.…”
Section: Gene Replacement Therapymentioning
confidence: 95%
“…126,127 MSCs are a type of adult stem cells 11 that have been intensively explored by Eliopoulos et al 128 for delivery of EPO to correct anemia successfully in mice. 129 We have previously transplanted MSCs derived from human Wharton's Jelly into the subretinal layer of the Royal College of Surgeon's rats and found that these cells had the ability to differentiate into retinal cells, which was in concurrance with other study.…”
Section: Future Directionsmentioning
confidence: 99%